MEDIA CONVERGENCE OF INDONESIAN HOUSE REPRESENTATIVE TELEVISION - Setiadarma, Dani; Rizkiansyah, Mariko (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2021)
The development of media convergence affects almost all the publication and broadcasting practices, including special media managed by the Indonesian House of Representatives (DPR). This article explores the practices of media management and communication patterns in DPR News Bureau. The research uses Dailey's media convergence model, namely the convergence of continuum model. Using case study method, we observe closely how staff's behavior and communication patterns among the media divisions of DPR. Interview conducted to find out how the editors run media management in providing information to the audience. The results showed that the editorial management of DPR media has applied the integrated media convergence; from collecting information, producing news to distributing the content. To cite this article (7th APA style):Setiadarma, D. & Rizkiansyah, M. (2021). Media convergence of the Indonesian house representative television. Journal Communication Spectrum: Capturing New Perspectives in Communication, 11(1), 74-83. http://dx.doi.org/10.36782/jcs.v1i1.2081